Effect of acute hyperglycaemia and/or hyperinsulinaemia on proinflammatory gene expression, cytokine production and neutrophil function in humans - Stegenga, M. E.; Crabben, S. N. van der; Dessing, M. C.; Pater, J. M.; Van Den Pangaart, P. S.; De Vos, A. F.; Tanck, M. W.; Roos, D.; Sauerwein, H. P.; Van Der Poll, T. (Diabetic medicine, 2008)
Aims  Type 2 diabetes is frequently associated with infectious complications. Swift activation of leucocytes is important for an adequate immune response. We determined the selective effects of hyperglycaemia and hyperinsulinaemia on lipopolysaccharide (LPS)‐induced proinflammatory gene expression and cytokine production in leucocytes and on neutrophil functions. Methods  Six healthy humans were studied on four occasions for 6 h during: (i) lower insulinaemic euglycaemic clamp, (ii) lower insulinaemic hyperglycaemic clamp, (iii) hyperinsulinaemic euglycaemic clamp, and (iv) hyperinsulinaemic hyperglycaemic clamp. Target levels of plasma glucose were 12.0 mmol/l (hyperglycaemic clamps) or 5.0 mmol/l (euglycaemic clamps). Target plasma insulin levels were 400 pmol/l (hyperinsulinaemic clamps) or 100 pmol/l (lower insulinaemic clamps). Results  Hyperglycaemia reduced LPS‐induced mRNA expression of nuclear factor of κ light polypeptide gene enhancer in B cells inhibitor alpha (NFKBIA), interleukin‐1 alpha (IL1A) and chemokine (C‐C motif) ligand 3 (CCL3), whereas during hyperinsulinaemia enhanced mRNA levels occurred in six out of eight measured inflammation‐related genes, irrespective of plasma glucose levels. Combined hyperglycaemia and hyperinsulinaemia led to enhanced IL1A, interleukin‐1 beta (IL1B) and CCL3 mRNA levels upon LPS stimulation. Neither hyperglycaemia nor hyperinsulinaemia altered cytokine protein production, neutrophil migration, phagocytic capacity or oxidative burst activity. Conclusions  These results suggest that short‐term hyperglycaemia and hyperinsulinaemia influence the expression of several inflammatory genes in an opposite direction, that the acute effects of hyperinsulinaemia on inflammatory mRNA levels may be stronger than those of hyperglycaemia, and that the effects of insulin, in particular, may be relevant in the concurrent presence of hyperglycaemia.